2007
DOI: 10.1038/ismej.2007.46
|View full text |Cite
|
Sign up to set email alerts
|

Population level functional diversity in a microbial community revealed by comparative genomic and metagenomic analyses

Abstract: In microbial mat communities of Yellowstone hot springs, ribosomal RNA (rRNA) sequence diversity patterns indicate the presence of closely related bacterial populations along environmental gradients of temperature and light. To identify the functional bases for adaptation, we sequenced the genomes of two cyanobacterial (Synechococcus OS-A and OS-B 0 ) isolates representing ecologically distinct populations that dominate at different temperatures and are major primary producers in the mat. There was a marked la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
226
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(233 citation statements)
references
References 45 publications
4
226
0
Order By: Relevance
“…Martiny et al (2006) also found that the gene content for phosphate acquisition was not congruent with rRNA phylogeny for members of Prochlorococcus. Likewise, extremely close relatives of hot spring Synechococcus have been shown to differ in their adaptations to light levels (Becraft et al, 2011) as well as phosphorus and nitrogen use pathways (Bhaya et al, 2007). Isolates of Pseudomonas, Acinetobacter (Choudhary and Johri, 2011) and Brevundimonas (Jaspers and Overmann, 2004), which had identical 16S rRNA gene sequences, were also found to occupy different ecological niches, with each using a unique combination of carbon substrates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Martiny et al (2006) also found that the gene content for phosphate acquisition was not congruent with rRNA phylogeny for members of Prochlorococcus. Likewise, extremely close relatives of hot spring Synechococcus have been shown to differ in their adaptations to light levels (Becraft et al, 2011) as well as phosphorus and nitrogen use pathways (Bhaya et al, 2007). Isolates of Pseudomonas, Acinetobacter (Choudhary and Johri, 2011) and Brevundimonas (Jaspers and Overmann, 2004), which had identical 16S rRNA gene sequences, were also found to occupy different ecological niches, with each using a unique combination of carbon substrates.…”
Section: Discussionmentioning
confidence: 97%
“…This has been demonstrated for resource traits such as particle colonization (Hunt et al, 2008), light adaptation (Moore et al, 1998;West and Scanlan, 1999;Johnson et al, 2006;Becraft et al, 2011) and nutrient use (Jaspers and Overmann, 2004;Martiny et al, 2006;Bhaya et al, 2007;Choudhary and Johri, 2011). This fine-scale association appears to hold true across the prokaryotic domains for genetically simple carbon use traits (Martiny et al, 2012); however, it is unknown whether extracellular enzyme traits also follow this pattern.…”
Section: Introductionmentioning
confidence: 97%
“…Cluster-1 contained scaffolds that were strongly associated with the Synechococcus spp. strains A and B 0 genomes, and included cyanobacterial phylogenetic marker genes and functional genes that were indicative of oxygenic photosynthesis, the Calvin-BensonBassham cycle and genes involved in nitrogen and phosphorus acquisition that were described previously (Steunou et al, 2006(Steunou et al, , 2008Bhaya et al, 2007). Most (86%) of these metagenomic sequences were jointly recruited and were more closely related to either the Synechococcus sp.…”
Section: Major Populations and Their Functional Potentialmentioning
confidence: 99%
“…The discovery of ferrous iron transporter homologs in Synechococcus sp. A-like populations (this study), and in B 0 -like populations (Bhaya et al, 2007), as well as the presence of these genes in the Roseiflexus sp. strain RS1 genome (van der Meer et al, 2010), suggests that the ability to use Fe 2 þ might be a common adaptation among the mat community members.…”
Section: Differences Between Metagenomes and Isolate Genomesmentioning
confidence: 99%
See 1 more Smart Citation